Depressive symptoms among children and adolescents in western china: An epidemiological survey of prevalence and correlates. (30th December 2016) - Wang, Lifei; Feng, Zhengzhi; Yang, Guoyu; Yang, Yaling; Wang, Kaifa; Dai, Qin; Zhao, Mengxue; Hu, Chaobing; Zhang, Rui; Liu, Keyu; Guang, Yu; Xia, Fan
Abstract: The aim of this study is to determine the prevalence and correlates of depressive symptoms in a school-based sample of 7–17-year-old children and adolescents in west-central China. A large cross-sectional sample survey of 10657 children and adolescents was conducted in Chongqing, a municipality in west-central China. Data were collected from the Children's Depression Inventory (CDI), Adolescent Self-Rating Life Events Checklist (ASLEC) and social-demographic variables which were evaluated with a structured scale. The total prevalence of depression risk was 23.9%. The risk factors for depressive symptoms included age older than 12 years, grade lower than 10, having unmarried parents, being taken care of by people other than two parents (single parent, grandparent(s), other relatives, or others), and living in a low-income family. The pressures of health and adaptation, interpersonal relationship, and study were also strong predictors of depressive symptoms. The prevalence of depressive symptoms among children and adolescents in Chongqing of China is relatively high compared with most figures reported in other cities. There is an urgent need to develop efficacious interventions aimed at the prevention and early recognition of childhood and adolescent depression. Highlights: We assess the prevalence in children and adolescents in west China with large samples. The overall prevalence is relatively high compared with previous report in China. Being older than 12-years and grade lower than 10 are risk factors for depression. Living in low income family is a strong predictor of depression. The pressure of interpersonal relationship, study, and health are risk factors.